Analisis Tindak Tutur Ekspresif pada Video “Learning by Googling” di dalam Kanal Youtube Sepulang Sekolah - Nilam Nathania; Hidayatun Toyibah Priyati Istu Utami; Aulia Rizky Nur Ruwita; Syafa Azmi Muazaroh; Fiki Nushrotul Hafidh; Asep Purwo Yudi Utomo; Ahmad Nurkhin (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Pragmatics is a field of linguistics that examines the relationship between speech acts between speakers and speech partners. In the study of pragmatics, there are many forms of speech acts and one of them is illocutionary speech acts. Illocutionary speech acts are further divided into several parts and one of them is expressive speech acts which researchers discuss in this study. This research aims to describe various theories regarding expressive speech acts, classify various types of expressive speech acts contained in the Learning by Googling video collection, and explain the forms of various types of speech acts contained in the Learning by Googling video collection. Researchers used two approaches, namely theoretical and methodological approaches. The theoretical approach that researchers use in this research is pragmatic because the topic is pragmatic studies, while the methodological approach that researchers use is a qualitative descriptive approach. The object of study used in this research is a collection of Learning by Googling videos on the Sepulang Sekolah YouTube channel. Researchers in collecting or collecting data use free listening and note-taking techniques. The data analysis technique is the matching technique. The matching technique or method is a technique or method used to identify the impact of the speaker's speech on the speech partner. Furthermore, in presenting the data the researcher used informal techniques. This article contains the results of research regarding the study of expressive speech acts which are applied to the study objects that researchers use and in which there are several forms of expressive speech, including praising, blaming, and criticizing. The benefit of this research is to provide knowledge about expressive speech acts that often occur in everyday life. It is hoped that readers will know and understand the science of expressive speech acts and can be a reference for writers of articles regarding expressive speech acts.